Relationship between ESL Learners’ Reading Self-Efficacy, Reading Strategies and Critical Reading among Pre-University Students in a Malaysia Public University (Sains Humanika, 2022)
Critical reading, suitable reading strategies and reading self-efficacy are vital factors in order to successfully understand and comprehend academic texts in tertiary institutions. Reading in the second language or foreign language is a complex process which demands the readers to commit cognitively and participate actively in the reading process. This study explores the relationship between reading self-efficacy, critical reading and use of reading strategies among pre-university students in Malaysia. The study involved 231 pre-university students in UTM (n=231). This study employed the quantitative descriptive research design. A set of questionnaires consisting of EFL Learners’ Self-Efficacy Scale in Reading, Survey of Reading Strategies and Peter Honey’s Critical Thinking Questionnaire weas distributed to the sample and the results from the descriptive analysis using frequency and percentage highlight that the students’ level of reading self-efficacy, critical reading and use of reading strategies were moderate, slightly above moderate and high, respectively. The findings from inferential statistical analysis using Spearman Correlation indicate the significant relationships between the three factors. Hence, the findings of this study could be used to develop a more appropriate and suitable curriculum incorporating explicit instructions to the use of reading strategies and critical reading. Furthermore, future studies could be done to develop a framework based on the hierarchical levels of cognitive demands to systematically monitor the students’ literacy development.
Keywords: Critical reading, reading self-efficacy, reading strategies, pre-university students